Fuzzy Logic Controller and Its Application in Brushless DC Motor (BLDC) in Electric Vehicle - A Review - Chico Hermanu Brillianto Apribowo; Musyaffa’ Ahmad; Hari Maghfiroh (Universitas Sebelas Maret (UNS), 2021)
Brushless DC motor (BLDC) is one type of electric motor that is widely used, especially in automotive systems. This motor is widely used as a driving force in electric vehicles. BLDC motor is chosen because it has the characteristics of high efficiency, reliability, and a wide speed range. Besides, BLDC motors require less maintenance and can operate quieter than DC motors. Even though it has many advantages, in its application the use of BLDC motors in electric vehicles is often less than optimal. The use of a conventional control system proportional integral derivative (PID) still has many weaknesses, especially in response to changes in load and track conditions. In this study, a control system was designed to regulate the speed of the BLDC motor, using a combination of Fuzzy and PID methods. Based on the results of the tests that have been done, the Fuzzy-PID control can provide better and more stable performance than using the conventional PI control.